2014
DOI: 10.1038/ismej.2014.64
|View full text |Cite
|
Sign up to set email alerts
|

Reprograming of gut microbiome energy metabolism by theFUT2Crohn’s disease risk polymorphism

Abstract: Fucosyltransferase 2 (FUT2) is an enzyme that is responsible for the synthesis of the H antigen in body fluids and on the intestinal mucosa. The H antigen is an oligosaccharide moiety that acts as both an attachment site and carbon source for intestinal bacteria. Non-secretors, who are homozygous for the loss-of-function alleles of FUT2 gene (sese), have increased susceptibility to Crohn's disease (CD). To characterize the effect of FUT2 polymorphism on the mucosal ecosystem, we profiled the microbiome, meta-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
169
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(188 citation statements)
references
References 74 publications
14
169
4
1
Order By: Relevance
“…18,19 In humans, deficiency of FUT2 -which occurs in around 20% of individuals, termed "nonsecretors" -is associated with shifts in microbial composition in the colonic mucosa, feces, and bile. [20][21][22][23] Tsyn deficiency could similarly affect microbial composition by altering nutrient sources and disrupting attachment sites for the intestinal microbiota.…”
mentioning
confidence: 99%
“…18,19 In humans, deficiency of FUT2 -which occurs in around 20% of individuals, termed "nonsecretors" -is associated with shifts in microbial composition in the colonic mucosa, feces, and bile. [20][21][22][23] Tsyn deficiency could similarly affect microbial composition by altering nutrient sources and disrupting attachment sites for the intestinal microbiota.…”
mentioning
confidence: 99%
“…In accordance with them, we discovered that high mRNA level of PTPN2 was significantly correlated with deep ulcer in CD patients ( Figure 5). As a signaling molecule, PTPN2 has a number of target genes including Janus kinases (JAKs), signal transducer and activator of transcription (STAT) 1 and 3, mitogen-activated protein kinase (MAPK) and epidermal growth factor receptor (EGFR) [39][40][41]. As mentioned above, IL17─JAK2─STAT3 and IL23R─JAK2 ─STAT3 pathway were essential for the function of Th17 in inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The first such studies in humans focused on specific genes and pathways, and have identified several significant microbiome-associated variants [41][42][43][44][45]. However, a potential shortcoming of the above studies is that they require previous knowledge of associated genes, and thus cannot discover new associations.…”
Section: Limited Power Of Microbiome Genome Wide Association Studiesmentioning
confidence: 99%